Non-polynomial representations of orthotropic tensor functions in the three-dimensional case: an alternative approach (Archives of Mechanics - Test, 1997)
The objective of this paper is to extend some of the results obtained in [1] to the three-dimensional case. Functional bases and generators for symmetric second-order orthotropic tensor functions are derived.